2011
DOI: 10.1128/jcm.01144-10
|View full text |Cite
|
Sign up to set email alerts
|

LysGH15, a Novel Bacteriophage Lysin, Protects a Murine Bacteremia Model Efficiently against Lethal Methicillin-Resistant Staphylococcus aureus Infection

Abstract: Phage-coded lysin is an enzyme that destroys the cell walls of bacteria. Phage lysin could be an alternative to conventional antibiotic therapy against pathogens that are resistant to multiple antibiotics. In this study, a novel staphylococcal phage, GH15, was isolated, and the endogenous lytic enzyme (LysGH15) was expressed and purified. The lysin LysGH15 displayed a broad lytic spectrum; in vitro treatment killed a number of Staphylococcus aureus strains rapidly and completely, including methicillinresistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 38 publications
(42 reference statements)
4
127
0
Order By: Relevance
“…76 Using a more potent staphylococcal endolysin (LysGH15) at the same concentration of~2 mg/kg offered the same level of protection from fatal bacteremia, but treatment could be extended up to an hour after MRSA challenge. 79 However, increasing potency was still unable to eliminate all bacterial burden. The added benefit of using LysGH15 over MV-L was its exceptional staphylolytic activity specifically toward MRSA strains.…”
Section: Staphylococcal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Using a more potent staphylococcal endolysin (LysGH15) at the same concentration of~2 mg/kg offered the same level of protection from fatal bacteremia, but treatment could be extended up to an hour after MRSA challenge. 79 However, increasing potency was still unable to eliminate all bacterial burden. The added benefit of using LysGH15 over MV-L was its exceptional staphylolytic activity specifically toward MRSA strains.…”
Section: Staphylococcal Infectionsmentioning
confidence: 99%
“…Gu et al suggested that the increased MRSA specific potency could be a result of greater binding by LysGH15 to cell wall moieties present only on methicillin-resistant strains. 79 In an attempt to show this, a LysGH15 CBD fused to GFP (LysGH15B-GFP) was constructed and tested on both methicillin-resistant and methicillin-sensitive S. aureus strains. Unfortunately, this methodology was unable to show different binding affinities between the 2 strain types.…”
Section: Staphylococcal Infectionsmentioning
confidence: 99%
“…We have previously described the staphylococcal phage GH15 (Gu et al, 2011). The complete genome (GenBank accession number JQ686190.1) was sequenced and analysed , revealing that a putative lysis module exists in the GH15 phage genome (Gu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The complete genome (GenBank accession number JQ686190.1) was sequenced and analysed , revealing that a putative lysis module exists in the GH15 phage genome (Gu et al, 2013). The lysin of GH15 (LysGH15) has been identified and the molecular mechanism of its lytic activity has been elucidated in previous studies (Gu et al, 2011(Gu et al, , 2014. However, the putative holin of GH15, as well as other homologous staphylococcal phage holins, has not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that 80a, phi 11, LysK, lysostaphin, 2638A, WMY, and vancomycin protected 100% of the animals from death, and Twort-or phiSH2-treated mice had less protection from systemic infection (50% -60% survivors), and P68 (administered in 20%) (55). the best time and dose of endolysin were 1h after post infection by injected intraperitoneally of GH15 lysin (56). A synergistic effect of Endolysins was also reported by Schuch et al in 2016, in an investigation of combination therapy with lysin CF-301 and daptomycin, vancomycin, oxacillin antibiotics for treating MRSA1 (29).…”
Section: Sepsismentioning
confidence: 98%